Ethnomedical Remedies among Slavic Speaking People in South Kosovo - Hajdari, Avni; Pieroni, Andrea; Jhaveri, Mamta; Mustafa, Behxhet; Quave, Cassandra (Ethnobiology and Conservation, 2018)
Local natural resources play an important role in securing human health in the Balkans, particularly as a source of food and medicine. The aims of this study were to document the ethnomedical practices of Slavic speaking groups in South Kosovo and to compare these findings to other studies conducted in the Western Balkans. Field research was conducted over a series of trips in 2014. Semi-structured interviews in which respondents were asked to list local taxa used for food and/or medicine were conducted in six communities located in the municipalities of Prizren and Dragash. Prior informed consent was obtained and 91 people were interviewed. Voucher specimens of cited wild flora and fungi were collected and deposited in duplicate at the herbaria of the University of Prishtina (Kosovo) and Emory University (USA). A total of 1,050 use citations were recorded for the various uses of 119 species (4 fungi and 115 plants) for food and/or medicine. Additionally, the ethnomedical uses of 27 ingredients of animal, mineral or industrial origin were also documented. The greatest number of citations were for dermatological and food uses of local plants. The most common families reported were Rosaceae (18 species cited), Lamiaceae (16) and Asteraceae (10). Informant consensus regarding category of use was highest (Fic ≥ 0.85) for the categories of oral health, dermatological, and otolaryngological applications. Both wild and locally cultivated plants continue to play an important role among various ethnic groups in South Kosovo, with 389 distinct applications documented in this study alone.